Introduction to the Special Issue on “Building Institutions for Priority Setting in Health” - Victoria Y. Fan; Javier Guzman; Pete Baker (Health Systems & Reform)
In the pursuit of universal health coverage, countries are invariably confronted with questions about which services to pay with public funds, to whom, and at what cost. Such priority-setting processes have major ramifications for the costs and benefits of care delivered. These processes are not just technical, but also highly political and organizational in nature and expressions of social values. This special issue focuses on building institutions for priority setting in health. These institutions serve a public purpose and are primarily concerned with conducting or using health technology assessment (HTA) to inform resource allocation decisions. We first define the concept of institutions for priority setting in health and the methodological considerations of assessing and evaluating these institutions. Next, we present key common themes and summarize key messages across the articles, including lessons learned and future challenges in building these institutions.